MECHANISMS OF THE ASSIMILATIVE PROJECT FOR AMAZIGH IDENTITY IN ALGERIA - Fadila CHEBABHA (Ziglôbitha)
Abstract : This study examines Algeria's approach to addressing Amazigh identity challenges through policies promoting linguistic and cultural diversity as pillars of national identity. Key measures include recognizing Amazigh as a national language in 2002 and an official language in 2016, establishing an Amazigh language academy, and engaging in dialogue with Amazigh movement representatives. Proactive steps followed the 2001 Amazigh Spring protests to address related issues. The findings reveal that these strategies helped accommodate Amazigh demands, fostering national cohesion by embracing diversity and reinforcing unity.